Uitgelicht : gedichten en foto's van de laureaten van de wedstrijd rond het thema "Ouder worden" en/of "holebi" 2009. - Het Holebihuis (Leuven : Het Holebihuis, 2009)
Fonds Suzan Daniel (FSD)
Nederlands
Brochure